Vivian Apple at the end of the world - Coyle, Katie (Houghton Mifflin Harcourt, 2015)
"Sixteen-year-old Vivian Apple returns home after the alleged 'Rapture' to find her devout parents gone and two mysterious holes in the roof. Vivian never believed in the Rapture, or the uber powerful Church of America. Now that she has been left behind, Vivan's quest for the truth begins"--